2020
DOI: 10.1002/itl2.167
|View full text |Cite
|
Sign up to set email alerts
|

Sending multiple packets per guaranteed time slot in IEEE 802.15.4 DSME: Analysis and evaluation

Abstract: Coping with bursty traffic is a common yet challenging task in the industrial Internet of Things (IoT). For example, 6LoWPAN is a standard that defines the integration of LoWPAN with IPv6, by fragmenting large IPv6 packets into several smaller MAC-layer packets. Therefore, it is necessary to envision message delivery mechanisms, which provide support for highly varying traffic. In this paper, we analyze sending multiple packets per guaranteed time slot (GTS) in IEEE 802.15.4 DSME to alleviate traffic during th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Another common way to improve reliability is seamless redundancy, 10 which is based on the idea to send the same data on different and disjoint communication channels. Other techniques are valid only in specific application conditions, for instance when traffic patterns are characterized by bursts 11 …”
Section: Current and Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common way to improve reliability is seamless redundancy, 10 which is based on the idea to send the same data on different and disjoint communication channels. Other techniques are valid only in specific application conditions, for instance when traffic patterns are characterized by bursts 11 …”
Section: Current and Future Trendsmentioning
confidence: 99%
“…The first paper “Sending multiple packets per guaranteed time slot in IEEE802.15.4 DSME: Analysis and evaluation” 11 investigates the DSME operating mode of the IEEE802.15.4 standard. It proposes optimizations for traffic patterns with burst.…”
Section: In This Special Issuementioning
confidence: 99%
“…For this, nodes wait for a maximum of an macAckMaxWaitDuration = 54 symbols for an acknowledgment frame (ACK) and retransmit the data packet if the ACK did not arrive in time. In a previous work we have shown that it is feasible and beneficial to transmit multiple packets per GTS [10].…”
Section: Overview Of Ieee 802154 Dsmementioning
confidence: 99%
“…These slots, so-called Guaranteed Time Slots (GTS), can be used for transmission of data packets. Multiple packets can be transmitted per GTS [10], however, every packet is individually acknowledged imposing a significant overhead in terms of throughput and energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In addition, the analysis of a MAC protocol is found very important in the cognitive radio networks. [12][13][14] Among all, the DSME mode [15][16][17] is the most preferred MAC scheme for a variety of applications such as home automation, factory automation, patient monitoring, habitat monitoring, smart metering, process automation, and smart homes. DSME MAC protocol is basically designed for the meshed network which extends to multihop and multichannel mode operation.…”
Section: Introductionmentioning
confidence: 99%